Advances in Immunotherapy for Pancreatic Cancer: 2013 - DeVito, Nicholas C; Saif, Muhammad Wasif (JOP. Journal of the Pancreas, 2013)
Pancreatic cancer is one of the more difficult malignancies to treat, and there is a great need for less toxic, effective regimens. Immunotherapy has shown potential in the treatment of pancreatic cancer, and at ASCO 2013 there were several progressive advances in its clinical application. Abstracts #3067, #3049, #3007, #4040, #LBA4004, and #3090 will be discussed. New developments in the field of immunotherapy are promising novel treatments for pancreatic neoplasms with tolerable side effect profiles. Image: Detail of immune response pathways induced following cytotoxic therapy.